Performance Assessment of a Permeable Reactive Barrier on Reducing Groundwater Transport of Nitrate from an Onsite Wastewater Treatment System - Charles P. Humphrey Jr.; Guy Iverson; Mike O’Driscoll (Hydrology)
Elevated concentrations of nitrate in potable water supplies have been linked to negative health outcomes such as methemoglobinemia and various cancers. Groundwater can become contaminated with nitrate from sources including onsite wastewater treatment systems (OWTSs). A groundwater well down-gradient from an OWTS serving an elementary school in Eastern North Carolina USA had 15 consecutive water samples collected over a 5-year period that exceeded the maximum contaminant level of 10 mg/L for nitrate. Corrective actions were required. A permeable reactive barrier (PRB) filled with woodchips was installed between the OWTS drainfield and the contaminated well. The concentration of nitrate in groundwater from the well steadily decreased after the PRB was installed, and a significant (p = 0.001) inverse correlation (−0.859) was observed between the mean annual nitrate concentration and years after the PRB. The nitrate concentration in groundwater from the well has been below 10 mg/L for the last 17 consecutive sampling events. The median nitrate concentration in the well was significantly lower (p = 0.007) post (6.93 mg/L) relative to pre (12.66 mg/L) PRB. The PRB has not required any maintenance over the past 10 years. The implemented PRB directly influences the sampling results from a monitoring well, but it is not necessarily confirmed that it intercepts the entire groundwater flow or fully prevents aquifer contamination. To confirm this, additional monitoring wells would need to be installed. This research has shown that PRBs can be an effective, low-maintenance, best-management practice to reduce the groundwater transport of nitrate.